2013
DOI: 10.1111/scs.12039
|View full text |Cite
|
Sign up to set email alerts
|

High‐frequency use of over‐the‐counter analgesics among adolescents: reflections of an emerging difficult life, a cross‐sectional study

Abstract: Adolescent, who are high-frequency users of over-the-counter analgesics, suffer more pain and have identifiable characteristics indicative of complex problems. Their ability to handle stress appears to be discordant with the kind of situations to which they are exposed. The wear and tear associated with allostatic mechanisms counteracting stress may heighten their pain experience.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 36 publications
2
39
0
Order By: Relevance
“…The CASP score for these ten studies ranges from five to nine for the six quantitative studies and from seven to nine for the four qualitative studies. Two articles Holager, Lagerløv, Helseth, and Rosvold () and Skarstein et al () are from the same data collection.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The CASP score for these ten studies ranges from five to nine for the six quantitative studies and from seven to nine for the four qualitative studies. Two articles Holager, Lagerløv, Helseth, and Rosvold () and Skarstein et al () are from the same data collection.…”
Section: Resultsmentioning
confidence: 99%
“…Holmström et al () also concluded that both parents and peers strongly influence adolescents’ use of OTCAs. Frequent pain from several part of the body, reduced self‐esteem, lack of sleep, school free time, frequent use of caffeine and alcohol were associated with use of OTCAs (Skarstein et al, ). Adolescents’ pain experiences and approaches towards handling pain were predictors for their use of OTCAS (Lagerlöv, Rosvold, Holager, & Helseth, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been stated in the literature that adolescents with authoritarian parents have decreased academic self‐esteem and family self‐esteem compared with adolescents with indulgent parents (Martinez & Garcia, ). In an earlier study, we found that adolescents with high use of OTCAs had lower self‐esteem and lower ambition for future education than did adolescents who seldom or never use OTCAs (Skarstein et al., ).…”
Section: Discussionmentioning
confidence: 82%
“…OTCA drug misuse is a global health challenge (Conca & Worthen, 2012;Groenewald, Essner, Wright, Fesinmeyer, & Palermo, 2014;Lessenger & Feinberg, 2008). High use of OTCAs among youth is associated with frequent pain from various parts of the body, reduced sleep, more part-time work and lower selfesteem (Skarstein et al, 2014). Continuous use of OTCAs to combat pain and to avoid stress can keep adolescents from learning healthier coping strategies.…”
Section: Introductionmentioning
confidence: 99%